FAMILY PANTOPHTHALMIDAE - Wolff, Marta; Ramos-Pastrana, Yardany; Vallejo, Fernando (Zootaxa, 2016)
This catalogue features 11 species distributed in 2 genera recorded to Colombia. Three species of Pantophthalmus are recorded for the first time to the country.